Carriage of Multidrug-Resistant Bacteria in Healthy People: Recognition of Several Risk Groups - Christel Neut (MDPI AG, 2021)
The increase in multidrug-resistant (MDR) bacteria in hospitalized people and the hospital environment has been thoroughly documented. In contrast, little is known about their presence in the community. However, increasing evidence is showing a high level of carriage in people without infectious signs. Colonized people can later develop infections due to MDR bacteria and may be able to transmit them to susceptible people (the number of which is increasing worldwide), for example, people with comorbidities such as diabetes, cancer, or inflammatory diseases and those in extreme age groups. Risk factors for the acquisition of MDR bacteria are as follows: (1) residence or travel in countries with high levels of MDR bacteria; (2) occupational risks such as health workers or people with close contact with animals (farmers, veterinarians) who frequently use antibiotics; and (3) comorbidities. Eradication is rather difficult and, thus far, has not shown clear-cut results. Preventive measures will be important in the future with a reinforcement of hygienic measures not only in the hospital, but also in the community.